2011
DOI: 10.3928/00220124-20101001-02
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Workplace Behavior to Inspire Learning: A Journey to Building a Learning Culture

Abstract: This article discusses the process of building a learning culture. It began with establishing acceptance and connection with the nurse unit manager and the ward team. In the early phases of developing rapport, bullying became apparent. Because bullying undermines sharing and trust, the hallmarks of learning environments, the early intervention work assisted staff to recognize and counteract bullying behaviors. When predominantly positive relationships were restored, interactions that facilitated open communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…This is in contrast to Clendon and Walker's (2012) participants who valued connections with others and actively sought to develop relationships with their nursing colleagues in the workplace. Satisfied connection was found to support students' learning (Schoonbeek and Henderson, 2011). Indeed, final year undergraduate nursing students in Kern et al (2014) study reported feeling a sense of belonging when they demonstrated competency while on clinical placement.…”
Section: Discussionmentioning
confidence: 92%
“…This is in contrast to Clendon and Walker's (2012) participants who valued connections with others and actively sought to develop relationships with their nursing colleagues in the workplace. Satisfied connection was found to support students' learning (Schoonbeek and Henderson, 2011). Indeed, final year undergraduate nursing students in Kern et al (2014) study reported feeling a sense of belonging when they demonstrated competency while on clinical placement.…”
Section: Discussionmentioning
confidence: 92%
“…There are some tangible or intangible resources to reward staff in the programmes, for example public praise, gifts. Mentor role modelling can encourage others to learn and make positive behavioural changes (Schoonbeek & Henderson, ; Vinales, ). Findings from this review highlight that traditional hierarchy is a barrier for mentees to listen to a mentor with the same job title.…”
Section: Discussionmentioning
confidence: 99%
“…[4,711] Interventions to mitigate nurse bullying are scarce. One study that discussed an intervention with promise used cognitive rehearsal.…”
Section: Introductionmentioning
confidence: 99%